THE INFLUENCE OF BUSINESS RISK ON CAPITALIZATION IN GOVERNMENT-OWNED BANKS - Pahlevi, Mohammad Reza; Africa, Laely Aghe (Ecopreneur.12, 2024)
This study aims to analyze and determine the effect of der, roe and interest rates on bank stock prices. Theindependent variables used in this study are the Debt to Equity Ratio, Return on Equity and interest rates. Whilethe stock price as the dependent variable. The population and sample in this study are conventional bankingcompanies listed on the Indonesian cstock exchange, totaling 8 companies for 7 years from 2014-2020. This studyuses secondary data using annual reports on www.idx.co.id and annual financial reports on the official website ofbanking companies. The sampling technique used purposive sampling. The data analysis technique uses multiplelinear regression. The results of this study state that simultaneously the three independent variables, namely Debtto Equity Ratio, Return on Equity, and interest rates have a significant effect on bank stock prices. Whilepartially Debt to Equity Ratio, Return on Equity, and interest rates have a positive effect on bank stock prices